1997
DOI: 10.1007/s004200050233
|View full text |Cite
|
Sign up to set email alerts
|

Types of organic solvents used in small- to medium-scale industries in Japan; a nationwide field survey

Abstract: Toluene remained the most common solvent and was used in combination with xylenes, ethyl acetate, and methanol. There was an increase in the use of dichloromethane as a degreasing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 47 publications
3
60
2
Order By: Relevance
“…Because more than one solvent was detected in most air samples (noting that the use of a mixture rather than unmixed individual solvent was common [7][8][9][10] ), the additiveness formula 11,12) was applied (including the cases of single solvent use), taking the measured concentration as a numerator and the ministry-defined administrative control level (ACL) 3) There were more than 2,000 employees in 9 enterprises, which are not shown in Fig. 1 [A].…”
Section: Measurement Of Solvent Vapor Concentrationsmentioning
confidence: 99%
“…Because more than one solvent was detected in most air samples (noting that the use of a mixture rather than unmixed individual solvent was common [7][8][9][10] ), the additiveness formula 11,12) was applied (including the cases of single solvent use), taking the measured concentration as a numerator and the ministry-defined administrative control level (ACL) 3) There were more than 2,000 employees in 9 enterprises, which are not shown in Fig. 1 [A].…”
Section: Measurement Of Solvent Vapor Concentrationsmentioning
confidence: 99%
“…United States' production of CCl 4 peaked at 1,200 million pounds in the early 1970s, then decreased steadily and production of CCl 4 was completely banned as of January 1, 2000 2) . The annual production volume of CCl 4 in Japan remained constant at about 50,000 tons from 1975 to 1993, and then declined rapidly 3) . However, a sizable volume of CCl 4 ranging from 60 to 300 tons/yr was still being imported to Japan in the years following 2000 3) .…”
mentioning
confidence: 99%
“…The annual production volume of CCl 4 in Japan remained constant at about 50,000 tons from 1975 to 1993, and then declined rapidly 3) . However, a sizable volume of CCl 4 ranging from 60 to 300 tons/yr was still being imported to Japan in the years following 2000 3) . A nationwide survey in Japan by Ukai et al 4) showed no use of CCl 4 as an organic solvent in small-and mediumscale industries in 1996, except for testing and research purposes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of sampling (with Tedlar bags) and analyses (by capillary gaschromatography) were as previously detailed elsewhere [1][2][3]6) . Group 3 solvents were not taken into account, as they are natural solvent mixtures and do not fit with the gaschromatographic identification 11,13) .…”
Section: Solvents Analyzed In Workroom Airmentioning
confidence: 99%